PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP KINERJA MELALUI MOTIVASI KERJA GURU DI SMK NEGERI 1 PUNGGING KABUPATEN MOJOKERTO - Wahyuni, Triana; Utari, Woro (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
The purpose of conducting this research is to prove and analyze the direct and indirect influence commitment and competence towards performance through teacher motivation at SMK Negeri 1 Pungging, Mojokerto City. This type of research is explanatory using quantitative methods. The population in this study were 120 teachers at SMK Negeri 1 Pungging using the slovin technique so that a sample of 92 was obtained. The data analysis technique was because it used Partial Least Square (PLS). The results of the study show that commitment is in the good category, competence are in the good category, performance is in the good category and teacher work motivation is in the good category. Commitment has a significant positive effect on performance. Competence have a no significant positive effect on performance. Commitment has a significant positive effect on teacher work motivation. Competence have a significant positive effect on teacher work motivation. Motivation has no significant positive effect on the teacher performance of SMK Negeri 1 Pungging, Mojokerto City Commitment has no significant positive effect on the performance through teacher motivation at SMK Negeri 1 Pungging, Mojokerto City. Competence has no significant positive effect on the performance through teacher work motivation at SMK Negeri 1 Pungging, Mojokerto City.